Torsional Vibration and Bifurcation Characteristics of Automotive Main Reducer Based on Nonlinear Hybrid Model. (October 2019) - Zou, Lin; Jia, Bing; Du, Mingya; Lie, Yujun; Xu, Jinli
Abstract: In the view of integrating dynamics of systems with dynamics of structures, the pinion shaft of automobile main reducer is divided into several torsion rod elements to establish its dynamic model, while the torsional vibration dynamic model of hypoid gears is still built with lumped mass method, thus the hybrid dynamic model of automotive main reducer is obtained by the combination of two kinds of dynamic models. Considering the nonlinear factors such as time-varying mesh stiffness, backlash and static transmission error of gear pairs, Runge-Kutta method is applied to obtain the time domain spectrum, spectrum graph, phase-plane diagram, Poincaré maps, and bifurcation diagrams of the system. The dynamic response characteristics of system with different parameters such as input rotational speed and mesh stiffness are systematically investigated by numerical simulations.